Recent Referees (Journal of Political Economy, 2021)
Previous articleNext article FreeRecent RefereesFull TextPDF Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Rajesh AggarwalLinda ArgoteRuediger BachmannJesse BackstromMartha BaileyDavid BaqaeeNicholas BarberisJean Noel BarrotShai BernsteinJavier BianchiAdrien BilalAlberto BisinAaron Bodoh-CreedAlessandro BonattiAlec BrandonThomas BuserLuigi ButeraJian CaiSteven CallanderRossella CalviOzan CandoganTimothy CasonSylvain ChassangHailiang ChenGabe Chodorow-ReichSouphala ChomsisengphetOlivier CoibionFabrice CollardJonathan ColmerLin William CongThomas CovertFlavio CunhaJan De LoeckerMark DeanPablo D’ErasmoRebecca Dizon-RossWioletta DziudaCatherine EckelNiklas EngbomChristine ExleyBenjamin FaberJesús Fernández-VillaverdeTeresa FortAlexander FrankelCary FrydmanOded GalorNicolae GârleanuNicolas Gendron-CarrierMatthew GentzkowBenjamin GolubGreer GosnellDavid GreenDaniel GreenwaldAdam GurenKareem HaggagMarina HalacMoshe HazanRandi HjalmarssonTom HoldenJustin HolzBo HonoréPeter HullDaniel HungermanErik HurstYoko IbukaEthan IlzetzkiYannis IoannidesOleg ItskhokiPhilippe JehielYoon JoJustin JohnsonMarcin KacperczykMatthias KehrigToru KitagawaNobuhiro KiyotakiAnton KorinekFabian KosseJoshua KriegerDarius LakdawallaTim LandvoigtJean-François LaslierMin Sok LeeEdwin LeuvenIlse LindenlaubMatthew LindquistLance LochnerMichael LovenheimYang LuUlrike MalmendierGonzalo MaturanaRosa MatzkinAndrew McClellanMichael McMahonKonrad MenzelBruce MeyerMoritz Meyer-ter-VehnPascal MichaillatKris MitchenerJarle MoenChristian MoserIsmael MourifiéJoseph MullinsCharles MurryScott NelsonLars NesheimDavid NeumarkSam NorrisDavid NovgorodskyMichaela PagelMallesh PaiAlessandro PavanJacopo PeregoNicola PersicoMichael PetersLaura PilossophIvan PngRobert PollakFranck PortierMichael PowellAndrea PratErik PrawitzLouis PuttermanMarek PyciaNancy QianVincenzo QuadriniJoão RamosA. ReynosoThomas RiveraArthur RobsonGuillaume RocheteauSutanuka RoyAnya SamekEstefania Santacreu-VasutEdouard SchaalSam Schulhofer-WohlJesse ShapiroRobin SicklesHolger SiegJoel SobelFrancesco SquintaniDouglas StaigerVincent SterkJoel StiebaleHelmut StixPhilip StrahanDavid StrombergMathieu Taschereau-DumouchelKonstantinos TatsiramosMarko TervioPetra ToddMartin UribeWinnie van DijkFrederic VermeulenXavier VivesPaul WillenChen YehJungwon YeoJunjian YiH. YoungMinchul YumYifan ZhangJin ZhouFabrizio ZilibottiGabriel Zucman Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 129, Number 3March 2021 Article DOIhttps://doi.org/10.1086/714170 Views: 540 © 2021 by The University of Chicago. All rights reserved. Crossref reports no articles citing this article.